Augmentation of Information Security by Cryptography in Cloud Computing - Suresh, K.Revana; Shasikala, Ch; Kumar, S.P (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing security challenges and it's additionally an issue to numerous analysts; first necessity was to concentrate on security which is the greatest concern of associations that are considering a move to the cloud. The points of interest of Cloud computing incorporate decreased expenses, simple upkeep and re-provisioning of assets, and consequently expanded benefits. Yet the appropriation and the section to the Cloud computing applies just if the security is guaranteed. Instructions to surety a finer information security furthermore in what manner would we be able to keep the customer private data secret? There are two real inquiries that present a test to Cloud computing suppliers. At the point when the information exchanged to the Cloud we utilize standard encryption routines to secure the operations and the stockpiling of the information. Anyhow to process information placed on a remote server, the Cloud suppliers need to get to the basic information. In this paper we are proposing Homomorphic encryption algorithm to execute operations on encoded information without decoding them which will give us the same comes about after computations as though we have worked straightforwardly on the basic information.